COMPARISON OF THREE ALUM HEMATOXYLIN – Harris, Mayer’s, Ehrlich hematoxylin using different tissues–A STUDY OF 60 CASES - Dr. Nilotpol Kashyap; Dr. Varun Rastogi; Dr. Nisha Maddhesiya; Dr. Nishant; Dr. Ashwini Dayma (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Objective: The aim of the study was to visualize and compare different alum hematoxylin and its histo-pathological picture, the clarity of staining and retention of stain inside the various tissues. Materials and Methods: The study included histological sections of four groups – Type I (well differentiated Oral squamous cell carcinoma), II (normal Lymph node), III (normal mucous acini), and IV (Fibroepithelial hyperplasia). The study comprised of 3 solutions – solution 1 (Harri’s hematoxylin), 2 (Mayer’s hematoxylin), 3 (Ehrlich’s hematoxylin). Each group of hematoxylin had sections of four groups. Hence, a total number of 60 sections were made. Results: The analysis of the relationship of the following variables, namely, different alum hematoxylin concluded that Harri’s hematoxylin was superior to Mayer’s and Ehrlich hematoxylin. Conclusion: Our study has shown much promise in exploring Hematoxylin and Eosinstain as a routine staining procedure. Further studies on Hematoxylin and Eosin could open a new horizon in the broad field of laboratory techniques. The persistence and continuing viability and growth of Hematoxylin and Eosin morphology indicates that this simple technique continues to meet most of the requirements of not only the pathologists but also clinicians, and, let us not forget, patients.